KAKI GAMBELAN JEGOG DALAM EKSPRESI KARYA SENI LUKIS - Putra, I Made Agus Darma; Jodog, I Made; Sujana, I Wayan (Program Studi Seni Murni ISI Bali, 2025)
This journal describes the creation of a painting that takes the theme “Gambelan Jegog Feet in the Expression of Painting”, which is inspired by the uniqueness of the jegog feet found in gambelan jegog in Jembrana. In general, this discusses the meaning contained in the jegog foot which is associated with the jegog tone element and the jegog gambelan player. The problem encountered is how to visualize the jegog foot, which is a sterilization of deer and buffalo feet, to represent ideas, notions, meanings and techniques used in realizing artworks. The method of creation is the process of realizing the work systematically. In this realization process, there are several methods that the author uses during the process of creating paintings, namely I Nyoman Wijaya's method: object observation, photo taking, object photo selection, drawing studies on paper media, sketches on canvas, background coloring, object coloring, and finally finishing. The author's goal in the creation of this work is to find out more about the jegog foot, which behind the simplicity of its shape, has its own philosophical meaning in it, as a medium for creativity and imagination into the form of paintings. The author applies the principles of fine art, thus creating 6 (six) works on this occasion in semester VI.